1968
DOI: 10.2134/agronj1968.00021962006000030016x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cropping Systems on Soil Physical Properties and Irrigation Requirements

Abstract: The irrigation requirements for the period May‐August were investigated in relation to some physical properties of Cecil soil as affected by eight cropping systems. These systems ranged from corn grown continuously with stalks removed to sod continuously. The cropping systems had no effect on particle size distribution and total porosity, but crust strength decreased and aggregate stability and infiltration rates increased as the quantity of plant material returned to the soil was increased. The increased wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1970
1970
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…Linear regression equations for corn yields and rainfall showed that yields of continuous corn and corn in rotation were increased 113. 6 ..,. 119.5 kg;'ha, respectively, for each centimeter of rainfall during June and July.…”
Section: Resultsmentioning
confidence: 99%
“…Linear regression equations for corn yields and rainfall showed that yields of continuous corn and corn in rotation were increased 113. 6 ..,. 119.5 kg;'ha, respectively, for each centimeter of rainfall during June and July.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 2, the amount of accumulated organic residue in the grass soil could supply appreciable microbial energy. Non-symbiotic N-fixing bacteria were shown to be present in the soil and on leaves of fescuegrass 3 • Fescuegrass root exudates, however, were found to be negligible from young fescue plants.…”
Section: Discussionmentioning
confidence: 94%
“…Carreker et al (3) conducted extensive crop rotation studies adjacent to this experiment and found that increasing the sod component in the cropping system increased stability of aggregates, decreased crust strength, and increased infiltration rates.…”
Section: Discussionmentioning
confidence: 99%
“…could well fail to establish a difference. Carreker et al (1968) sampled at only one depth in the topsoil and failure to show a difference between soil under grass and soil under corn may have been caused by this.…”
Section: Discussionmentioning
confidence: 99%